วัดงาม นามมงคล: แนวทางการพัฒนาการท่องเที่ยวเชิงศาสนาของวัดนามมงคล ในเขตอำเภอเมือง จังหวัดเชียงใหม่; Religious Tourism Development Guidelines for Auspicious-Name Temples in Muang District, Chiang Mai Province: Religion Tourism Development of Auspicious Name Temples in Chiang Mai - พืชทองหลาง, ประทีป; ประสิทธิ์บุรีรักษ์, เพราพิลาส; พืชทองหลาง, ญาตาวีมินทร์ (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2018)
งานวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาประวัติ ความเชื่อของพระเจดีย์และพระพุทธรูปของวัดนามมงคล 2) เพื่อศึกษาศักยภาพของแหล่งท่องเที่ยวเชิงศาสนาของวัดนามมงคล 3) เพื่อเสนอแนวทางการพัฒนาแหล่งท่องเที่ยวเชิงศาสนาของวัดนามมงคล รูปแบบการวิจัยเป็นแบบผสานวิธี ระหว่างการวิจัยเชิงปริมาณและการวิจัยเชิงคุณภาพ พื้นที่วิจัย คือ วัดนามมงคลในจังหวัดเชียงใหม่ 9 วัด ได้แก่ วัดลอยเคราะห์ วัดดับภัย วัดดวงดี วัดศรีเกิด วัดชัยพระเกียรติ วัดหมื่นเงินกอง วัดหมื่นล้าน วัดปราสาท และวัดเชียงมั่น กลุ่มตัวอย่าง 420 คน แบ่งเป็นนักท่องเที่ยว 400 คน ใช้วิธีคัดเลือกแบบบังเอิญ และผู้มีส่วนเกี่ยวข้อง 20 คน ใช้วิธีคัดเลือกแบบเจาะจง เครื่องมือวิจัยมี 3 ชนิด คือ แบบสอบถาม แบบสังเกต และแบบสัมภาษณ์ การวิจัยเชิงปริมาณ วิเคราะห์ข้อมูล จากแบบสอบถามด้วยโปรแกรมคอมพิวเตอร์สำเร็จรูป สถิติที่ใช้ ได้แก่ ร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน ส่วนการวิจัยเชิงคุณภาพ ใช้การวิเคราะห์ สังเคราะห์เนื้อหาจากแบบสังเกต และการสัมภาษณ์ แล้วเขียนบรรยายเชิงพรรณนา ผลการวิจัยพบว่า 1) พระเจดีย์และพระพุทธรูปวัดนามมงคลมีความเก่าแก่ มีเรื่องราวที่เกี่ยวเนื่องกับที่มาของชื่อที่เป็นมงคล และมีความเกี่ยวเนื่องกับประวัติศาสตร์ของเมืองเชียงใหม่ 2) นามของวัด พระเจดีย์ และพระพุทธรูปเป็นนามมงคลที่เป็นสิ่งดึงดูดใจนักท่องเที่ยว รวมถึงประวัติความเก่าแก่ ความศักดิ์สิทธิ์ ความงดงามวิจิตรทางศิลปกรรมแบบล้านนาเป็นจุดแข็งของวัดนามมงคลทั้ง 9 แห่ง 3) แนวทางการพัฒนาแหล่งท่องเที่ยววัดนามมงคลควรให้ความสำคัญ 5 ประการ คือ 1) ส่งเสริมสติ 2) สะอาด 3) สุขสบาย 4) สงบเย็นใจ และ 5) สัปปายะ Abstract This research was conducted for the following objectives: 1) to study the history, beliefs towards pagodas and Buddha images of auspicious-name temples, 2) to study the potential of temples as religious tourism destinations, and 3) to find approaches to developing temples for religious tourism. The research combines methods of quantitative research and qualitative research. The research areas comprised nine auspicious-name temples in Chiang Mai which are Wat Loi Khro, Wat Dubphai, Wat Duang Dee, Wat Sri Goed, Wat Chai Prakiat, Wat Muen Ngen Kong, Wat Muen Lan, Wat Pharsat, and Wat Chiang mun. A sample group consisted of 400 tourists using accidental sampling and 20 participants using purposive sampling. Research tools which were a set of questionnaires, non-participant observation form, and standardized interview form were used for data collection. Obtained data were analyzed by using descriptive statistics comprising percentage, mean, and standard deviation. The results showed that 1) the pagodas and Buddha images of auspicious-name temples were old and had stories related to the origin of the name and also relevant to the history of Chiang Mai, 2) the name of the temple, pagodas and Buddha images had auspicious names and attracted tourist, including the ancient history, holiness, and beauty of fine arts of Lanna, and 3) guidelines for tourism development of auspicious-name temples should consider 1) conscience, 2) cleanliness, 3) comfort, 4) tranquility, and 5) suitability.